2015
DOI: 10.3389/fmech.2015.00008
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Mode Design with High Efficiency and Low Emissions Controlled by Mixtures Stratification and Fuel Reactivity

Abstract: (2015) Combustion mode design with high efficiency and low emissions controlled by mixtures stratification and fuel reactivity. Front. Mech. Eng. 1:8. doi: 10.3389/fmech.2015.00008 Combustion mode design with high efficiency and low emissions controlled by mixtures stratification and fuel reactivity This paper presents a review on the combustion mode design with high efficiency and low emissions controlled by fuel reactivity and mixture stratification that have been conducted in the authors' group, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The effects of fuels with different premixed ratios on the in-cylinder pressure, heat release rate (HRR) and integrated heat release (IHR) at an IAT of 50 • C in RCCI combustion mode are shown in Figures 4 and 5. In RCCI, the ignition timing is delayed with the increase in low-reactivity fuel, resulting in a reduction in in-cylinder pressure [48]. When the data obtained at a 2500 rpm engine speed and lambda value of 2.40 are analyzed, it can be stated that the maximum in-cylinder pressure increases with the use of a premixed fuel (PR25) with higher reactivity.…”
Section: Premixed Ratio Effectsmentioning
confidence: 99%
“…The effects of fuels with different premixed ratios on the in-cylinder pressure, heat release rate (HRR) and integrated heat release (IHR) at an IAT of 50 • C in RCCI combustion mode are shown in Figures 4 and 5. In RCCI, the ignition timing is delayed with the increase in low-reactivity fuel, resulting in a reduction in in-cylinder pressure [48]. When the data obtained at a 2500 rpm engine speed and lambda value of 2.40 are analyzed, it can be stated that the maximum in-cylinder pressure increases with the use of a premixed fuel (PR25) with higher reactivity.…”
Section: Premixed Ratio Effectsmentioning
confidence: 99%
“…Turbo-charging can be a good option to increase the amount of air available for combustion and volumetric efficiency can also be increased. [22] For RCCI engines, the stable operation can be achieved by high charge reactivity under low load conditions. On the contrary Peak Pressure Rise rate can be suppressed by use of low charge reactivity.…”
Section: Articlementioning
confidence: 99%
“…The early and late direct and port fuel injection strategies have already been discussed in table 1. Reitz et al, Paykani et al and Wang et al[20][21][22] studied the articles related to the development of RCCI engines.…”
mentioning
confidence: 99%
“…Supplying two fuels which have different combustion characteristics (reactivities) can be used to control the combustion phasing, combustion duration and engine knock [51][52][53]. This is called as Reactivity Controlled Compression Ignition (RCCI), one of the techniques used in HCCI mode.…”
Section: Fuel Reactivity Controlmentioning
confidence: 99%
“…High reactive fuel is generally the one that has high cetane number to initiate combustion. Low reactive fuel is being port injected which generally has high octane number to bear the engine compression ratio in order to reduce knock [53]. It was reported that gasoline has high octane number-100 [57] and it can be used as low reactive fuel.…”
Section: Rcci With a Port And Direct Injection (Single Fuel)mentioning
confidence: 99%